The Atlas of The Bible and The History of Christianity - Tim Dowley (UK The British and Foreign Bible Society, 1997)
The section headings are: the Old Testament Period; New Testament Period: the early Church (from the spread of Christianity to the Hussites): the modern Church (from the voyages of discovery to Christianity in Asia)
150 Full-Colour Maps 50 Full-Colour Photos
Keywords: Biblical Studies (3ebOeGJ hOQGSGJ GdcJGH GdebOSs; Bible